Melanin‐Inspired Organic Electronics: Electroluminescence in Asymmetric Triazatruxenes. Issue 6 (4th March 2015) - Manini, Paola; Criscuolo, Valeria; Ricciotti, Laura; Pezzella, Alessandro; Barra, Mario; Cassinese, Antonio; Crescenzi, Orlando; Maglione, Maria Grazia; Tassini, Paolo; Minarini, Carla; Barone, Vincenzo; d'Ischia, Marco
Abstract: The oxidative polymerization of 5, 6‐dihydroxyindoles and related hydroxyindoles at pH<3 is diverted from the usual eumelanin‐forming pathway to produce mixtures of symmetric and asymmetric triazatruxenes (TATs), which could be separated and characterized for their opto‐electronic properties with the aid of TD‐DFT calculations. Data showed that the asymmetric isomers exhibit higher fluorescence quantum efficiencies, lower HOMO–LUMO gaps, better film homogeneity, and a more definite aggregation behavior than the symmetric counterparts, suggesting promising applications in organic electronics. The enhanced luminance exhibited by the OLED devices fabricated with blends of the synthesized TATs in poly‐9‐vinylcarbazole confirmed the potential of the asymmetric skeleton as new versatile platform for light‐emitting materials. Abstract : From black melanins to light‐emitting triazatruxenes : Melanin‐inspired triazatruxenes have been synthesized and their opto‐electronic properties studied (see figure). The comparision of the electroluminescence and luminance of the OLED devices fabricated with triazatruxenes suggests the potential of the asymmetric platform as a new central core for light‐emitting materials.